Analisis Strategi Bisnis Pada Perusahaan Inspeksi Dalam Industri Jasa Inspeksi Teknis Di Indonesia - Mayella Lusiana Gunawan (Universitas Tarumanagara, 2019)
The objectives of the study are: (a) to identify internal and external factors affecting Inspection Company in the technical inspection services industry; (b) to find the suitable and effective business strategy for Inspection Company in order to increasing sales performance in the strong competition environment. Data collection techniques required in this study is using primary data (information and data) (case studies and literature). The first step to be done in this research is the input stage, followed by the Matching Stage, and the last stage is the decision analysis. The Result of the research are: (a) recommended strategy for Inspection Company is product development; (b) the second recommendation of the business strategy is horizontal integration.